Ovarian Cancer: The Role of Functional Imaging as an End Point in Clinical Trials. Issue 6 (1st July 2010) - Sala, Evis; DeSouza, Nandita; Lee, Susanna I.; Atri, Mostafa; Hricak, Hedvig
Abstract : The Gynaecological Cancer InterGroup conducts collaborative trials in gynecologic cancer and also aims to develop standards that can be used to strengthen all aspects of study methodology. There is an urgent need to develop more refined imaging end points that can be used as early treatment response biomarkers in ovarian cancer. Therefore, the Gynaecological Cancer InterGroup commissioned an expert position paper on the role of functional imaging as an end point in clinical trials in ovarian cancer. In this position paper, we state the limitation of current anatomical imaging methods used in clinical trials, highlight the potential of functional imaging, and provide key recommendations on the use of functional imaging as an end point in ovarian cancer clinical trials.